If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p * 3 + 6 = 0 Reorder the terms for easier multiplication: 2 * 3p + 6 = 0 Multiply 2 * 3 6p + 6 = 0 Reorder the terms: 6 + 6p = 0 Solving 6 + 6p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6p = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 6p = 0 + -6 6p = 0 + -6 Combine like terms: 0 + -6 = -6 6p = -6 Divide each side by '6'. p = -1 Simplifying p = -1
| 2+-6k+13k*13k+92k*92k*92k= | | 9x-6y=16 | | 3995=ln(0.25x) | | 8d-1=21 | | 3k*3k-8k+6k*6k*6k+2k-5k*5k*5k+k*k*k+2k*2k+5-3= | | 1x+6+9+15=29 | | 9(m+1)=24 | | (H-6)+20=-4 | | y^2-20y=90 | | 25-d+2d-14= | | 3x+5=61 | | 4(3b-1)+6=5(b+4) | | 15a*15a+ab-6b*6b-2a*2a-5ab-2a*2a+4ab+b*b= | | 80=4(2x-3)+20 | | x(2x+1)=19 | | 6n-4=3n+8 | | 8x+11-3x=46 | | x-4/4-1=x-12/5 | | 1/2x-5=5/8x | | 4(5x+10)-16x+8=40 | | a+12-3a+4a-30= | | p*p-p*p*p*p-p*p*p+2p*2p*2p+4p*4p*4p*4p-3p*3p+3p*3p= | | x^2+0.03x-0.91=0 | | (12-x)(x+1)(x-1)=160 | | in(x)+in(2-x)=0 | | b/8-6=10 | | 7x-5=10+2x | | (100-10)*c=45 | | 5(8x-6)=34 | | y^2+100=0 | | -2(9x-7)+12=8 | | a/2+5=11 |